2019
DOI: 10.1177/1475725719869164
|View full text |Cite
|
Sign up to set email alerts
|

Open Science Promotes Diverse, Just, and Sustainable Research and Educational Outcomes

Abstract: Open science initiatives, which are often collaborative efforts focused on making research more transparent, have experienced increasing popularity in the past decade. Open science principles of openness and transparency provide opportunities to advance diversity, justice, and sustainability by promoting diverse, just, and sustainable outcomes among both undergraduate and senior researchers. We review models that demonstrate the importance of greater diversity, justice, and sustainability in psychological scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…The issue of under-resourced institutions deserves special attention (Grahe et al, 2020). Most research in the U.S. comes out of large public land-grant universities or research-intensive private institutions.…”
Section: Collaborationmentioning
confidence: 99%
“…The issue of under-resourced institutions deserves special attention (Grahe et al, 2020). Most research in the U.S. comes out of large public land-grant universities or research-intensive private institutions.…”
Section: Collaborationmentioning
confidence: 99%
“…Although evaluating the contributions of various open science initiatives toward advancing DJS for students, we recently constructed a brief set of questions to guide our evaluations (Grahe et al, 2019). These questions are presented online (https://osf.io/qv8nt/) and provide a framework by which to examine research efforts of individuals or groups.…”
Section: Applying a Djs Lens To This Special Issuementioning
confidence: 99%
“…During my Psi Chi Presidency (2016-17), I organized a symposium at the American Psychological Association about how "Open Science Initiatives Promote Diverse, Just, and Sustainable Research." A subsequent APS symposia with the same title but different speakers inspired a student to expand on the topic for part of her PhD qualifying exams (Cuccolo, 2019), a manuscript under review (Grahe, Cuccolo, Leighton, & Alvarez, 2019), and other conversations that indirectly led to this special issue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For OpenScholarship, there has been relatively little explicit work into the underlying principles (with the exception of the dozens of declarations and charters aimed at OA), and especially regarding those that are universally accepted. A recent review of Open Science demonstrated that it can help to advance diversity, justice and sustainability in the psychological sciences(Grahe et al 2019). Beyond this, OCSDNet is almost unique in this space, in that it proposes seven principles for Open and Collaborative Science as part of its Open Science Manifesto .…”
mentioning
confidence: 99%